Community participation and empowerment in primary education - Govinda, R.; Diwan, Rashmi (New Delhi ; Thousand Oaks, Calif. : Sage Publications, 2003)
It is recognized that community participation can play an important role in promoting primary education. This volume presents the experiences, problems encountered, and lessons learnt from initiatives launched in 5 Indian states - Madhya Pradesh, Karnataka, Rajasthan, Bihar and Kerala. It is for those involved with education and social work.
Introduction - R Govinda and Rashmi Diwan Emerging Issues and PracticesCommunity Participation in School Education - P K Michael Tharakan Experiments in the State of KeralaCommunity Participation and Empowerment in Primary Education - Vimala Ramachandran Discussion of Experiences from RajasthanCommunity Participation and Literacy - Sadhna Saxena Beyond SemanticsThe Community in Charge - Anjali Noronha Shades of Experience from Madhya PradeshDynamics of Community Mobilization in a Fragmented and Turbulent State - Vinay K Kantha and Daisy NarainCommunity Participation in Primary Education - N Shantha Mohan, M D Gayathri Devi Dutt and Piush Antony The Karnataka ExperienceMaking Sense of Community Participation - Vinod Raina Comparing School Education and Watershed DevelopmentDynamics of Decentralized Management in Primary Education - R Govinda Policy and Practice in Rajasthan and Madhya PradeshCapacity Building for Educational Governance at Local Levels - R Govinda
Includes bibliographical references and index.
BIED
Keywords: Community and school -- India; Education, Elementary -- India; Literacy -- India